Perkembangan Akuntansi dalam Menghadapi Pesatnya Kemajuan Teknologi - Puspa, Citra (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This research aims to see whether the rapid advancement of technology has a positive impact on accounting science, especially the accounting profession, or vice versa, this technological development has a negative impact on accounting science, especially the accounting profession. This type of research is qualitative research with a descriptive approach. The source of data in this research is a literature study of the thoughts and opinions of experts and practitioners in the field. The results of this study indicate that the development of the world of technology must be applied in the world of accounting in order to improve the quality of accounting itself, but it is concluded that accounting cannot be replaced by technology. Technology only simplifies and accelerates the process of accounting but cannot replace the role of accounting science and the accounting profession or an accountant.